PENGARUH SETTING RUANG KFC MEGAMAS TERHADAP PERILAKU PENGUNJUNG DENGAN PENDEKATAN BEHAVIOR MAPPING - Bakhtiar (Universitas Bina Taruna Gorontalo, 2025)
This study aims to identify the influence of the physical spatial setting on visitor behavior at KFC Megamas Manado. The research employs a descriptive qualitative method with a behavioral approach. Data collection techniques include observations, measurements of the existing building conditions, and the creation of a layout plan map as an instrument for behavior mapping through the place-centered mapping technique, along with documentation of the physical environment setting and physical traces left by visitors. Based on the analysis, several physical factors or environmental attributes were found to influence visitor behavior, namely: comfort, privacy, control, and legibility. These findings indicate that similar or identical physical spatial settings tend to produce relatively similar behavior patterns.